2013
DOI: 10.1159/000354098
|View full text |Cite
|
Sign up to set email alerts
|

Genome Duplication in Early Vertebrates: Insights from Agnathan Cytogenetics

Abstract: Agnathans represent a remnant of a primitive offshoot of the vertebrates, and the long evolutionary separation between their 2 living groups, namely hagfishes and lampreys, could explain profound biological differences, also in karyotypes and genome sizes. Here, cytogenetic studies available on these vertebrates were summarized and data discussed with reference to the recently demonstrated monophyly of this group and to the 2 events of whole genome duplication (1R and 2R) characterizing the evolution of verteb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 81 publications
2
19
0
Order By: Relevance
“…The chromosomal locations of the two scaffolds and divergence of the two genes have not been resolved. It is not clear whether they have been duplicated from a common gene, either by a whole genome duplication (Caputo Barucchi et al, 2013;Mehta et al, 2013) or a lineage-specific duplication event as seen for the Hox gene family (Force et al, 2002). The genomic clustering of the ACKR3/CXCR7 gene with IQCA1 is conserved among all jawed vertebrates examined (Fig.…”
Section: Ackr3/cxcr7 and Other Ackrsmentioning
confidence: 99%
See 1 more Smart Citation
“…The chromosomal locations of the two scaffolds and divergence of the two genes have not been resolved. It is not clear whether they have been duplicated from a common gene, either by a whole genome duplication (Caputo Barucchi et al, 2013;Mehta et al, 2013) or a lineage-specific duplication event as seen for the Hox gene family (Force et al, 2002). The genomic clustering of the ACKR3/CXCR7 gene with IQCA1 is conserved among all jawed vertebrates examined (Fig.…”
Section: Ackr3/cxcr7 and Other Ackrsmentioning
confidence: 99%
“…In river lamprey (Lampetra fluviatilis), an orthologue of CXCL8 has been characterised and is expressed in lymphocyte like cells (Najakshin et al, 1999), and its candidate receptor(s) could be one of the homologous receptor genes found in sea lamprey. Agnathans are proposed to have undergone the 1R whole genome duplication followed by an additional lineage specific genome duplication (Caputo Barucchi et al, 2013;Lagman et al, 2013;Mehta et al, 2013) and have a non-canonical adaptive immune system based upon leucine-rich repeat containing receptors (Cooper and Herrin, 2010). It can be hypothesised that the emergence of the chemokine system might be associated with this major evolutionary change in immune defences, to regulate the diverse populations of immune cells appearing at this time (DeVries et al, 2006).…”
Section: Origin Of Vertebrate CXC Chemokine Receptorsmentioning
confidence: 99%
“…The results of the slot-blot analysis indicate that the LCA-ApaI sequence is well conserved in Petromyzontidae and Mordaciidae, but not in Geotriidae. Mordaciidae, which is distributed in the southern hemisphere, has a lower chromosome number (2 n  = 76) than Petromyzontidae (2 n  = 142–174) in the northern hemisphere and Geotriidae (∼180 chromosomes) in the southern hemisphere, suggesting that extensive centric fusions occurred in Mordaciidae 9 , 13 . Molecular phylogenetic analyses suggested that Mordaciidae is in a separate clade from Petromyzontidae and Geotriidae, 40–43 which is reflected by the difference in chromosome numbers between Petromyzontidae/Geotriidae and Mordaciidae.…”
Section: Discussionmentioning
confidence: 99%
“…Species of Geotriidae and Petromyzontidae have 142–184 chromosomes, whereas Mordaciidae species have 76 chromosomes 7–14 . However, the chromosome number in hagfishes is much smaller and variable (2 n  = 14, 28, 34, or 36) 11 , 13 . The GC-content of 4-fold degenerate sites (GC 4 ) in the protein-coding regions also differ greatly between lampreys and hagfishes; GC 4 is much higher in lampreys than in hagfishes 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Other species such as lamprey or hagfish, which could provide important perspectives on inter-2R genome evolution (Caputo Barucchi et al ., 2013; Mehta et al ., 2013), and Asymmetron lucayanum , which may be the most basal chordate discovered (Yue et al ., 2014), have only partial genomes available. The arrangement of genomic data onto chromosomes and annotation of the genes of these species would provide a large boon to vertebrate evolutionary research.…”
Section: Phylogeny and Synteny For Delineating Gene Family Emergencementioning
confidence: 99%